2022
DOI: 10.1155/2022/2900378
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrasound Comparative Analysis of Coronary Arteries before and after Immune Blocking Therapy with Gamma Globulin in Children with Kawasaki Disease

Abstract: Objective. To investigate the ultrasound characteristics and clinical efficacy of coronary arteries before and after immune blocking therapy with gamma globulin in children with Kawasaki disease. Methods. A total of 64 children with Kawasaki disease who were treated in our hospital from January 2018 to October 2021 were selected. All the children were given immune blocking therapy with gamma globulin on the basis of conventional treatment. The disappearance time of related symptoms and signs (fever, mucosal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%